Al-Qur’an Antara Wahyu Aural dan Kodifikasi ‘Uthmānī - Jauhar Azizy; Muhammad Sairi (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2018)
This study will begin by discussing the history of the Qur’an, the Qur’an as a revelation, the history of the writing of the Qur’an and the content of the discussion of the Qur’an. By describing what the initial scriptures were written about and when the general codification of the Koran was agreed upon became the main global reference, it could be understood by educated people, especially the laity. As we already know that the Koran in general is initially a complex thing, meaning that the process of occurrence requires stages that are not instantaneous. Various concepts related to the scriptures, such as “God, Angels, Revelations, Prophets,” are often understood as taken forgranted. Likewise the process of revelation of the Qur’an, such as narration, writing, gathering and opening, is often not a concern. This paper intends to discuss the Qur’an from a Historical-Theological perspective. Other things accepted in dogma, such as God's word, verse structure, spelling, and structure of the text, are questioned again by positioning in the historical context at the time the revelation was revealed and then written. The emphasis of this paper is on the process of sacralization of the Koran having a long journey and intersecting with the historical events of the Muslims between the aural and the codification of ‘Uthmānī. Briefly, outlining the history of revelation and writing of the Koran becomes a “holy book” for religious communities. The process of sacralization of the